Living Hadis tentang Adab terhadap Guru di UIN Sunan Kalijaga Yogyakarta: Internalisasi Nilai dan Tantangan Modernitas - David Ricardo; Amri Saputra; Khairul Amin; Ansorul Alim; Ridwan Faqih Sihono; Marhumah (MAN 4 Kota Pekanbaru, 2025)
The hadith on respect toward teachers occupies a vital role in Islamic education, emphasizing that proper adab is the key to the blessing of knowledge. This study aims to examine how the hadith on teacher respect is understood and practiced within the academic culture of UIN Sunan Kalijaga Yogyakarta. Using a qualitative approach within the living hadith framework and a phenomenological perspective, data were collected through observation, interviews, and documentation involving lecturers and students. Thematic analysis shows that the hadith is internalized as moral and spiritual ethics forming an academic habitus characterized by politeness, reverence, and moral exemplarity. The local ngajeni culture strengthens this process, aligning with Islamic ethical teachings. However, digital modernity presents egalitarian challenges that tend to weaken traditional respect. The study recommends revitalizing adab education through leadership, policy, and curriculum integration in Islamic higher education.